Management of basal rot disease ("moler") of shallot with biomanci fertilizer - Wiwiek Sri Wahyuni; Ali Wafa; Suhartiningsih Dwi Nurcahyanti; Dodo Brilliant Priandono (Agrovigor, 2023)
Shallots are often infected by fusarium basal rot (local name: Moler disease), generate by the soil borne fungi, Fusarium oxysporum f. sp. cepae. The 35-45 days after planting was vulnerable time for shallot on it disease. However, the infection process can start more early on susceptible seed. Study aim to understand the effectivity of mixture of Indian Bael, Local name Maja fruit (Aegle marmelos) and rabbit urine (Biomanci) were used as organic fertilizer and it capability to control Moler disease. Result showed the biomanci fertilizers on all treatments had no effect on the severity and incidence of plant diseases. Although there was a decrease in severity in biomanci treatment 15 and 20% at 6 week but it was not significant. The increase in disease severity was triggered by favorable weather for the development of the disease, a high rainfall and by the arrival of flooding at the study site. As a result, the AUDPC value which is in the range 250 indicates that the plant was at a vulnerable level of resistance. Disease suppression efficacy was 12-18% means that biomanci was less effective in controlling Moler disease. It was concluded that although biomanci can be used as a biopesticide, in this study biomanci acts more as a fertilizer than as a biopesticide in blue Lancor variety, which is susceptible shallot, with a small disease suppression efficacy value of 12.03%..